Tunnel‐induced impact ionization in the metal–thin‐insulator‐semiconductor–metal system - Dixit P.N.; Lal P.; Srivastava S.K. (My University, 2025)
A simplified expression relating the current density and the bias‐voltage has been obtained for the metal–thin‐insulator‐semiconductor‐metal (MISM) system. Numerical calculations are made for Al–(Al2O3)–CdS–Al systems for different values of thickness of the insulator region and of donor densities. An approximate relation between current and voltage is also proposed to fit the theoretically calculated values. The experimental studies are found to be in some agreement with the proposed equation. Copyright © 1975 WILEY‐VCH Verlag GmbH & Co. KGaA